Integrating societal concern into an EU regulatory proposal for new genomic techniques in food crops using association rules - Iuri Peri; Federica Consentino; Alessandro Grasso; Gabriella Vindigni (Agriculture & Food Security)
Abstract Ensuring global food security is an increasingly complex challenge, prompting researchers and the agri-food industry to explore biotechnological solutions. Over the past decade, New Genomic Techniques (NGTs) have transformed plant breeding by enhancing yields, disease resistance, and climate adaptability. Despite these innovations, NGTs remain regulated under the same framework as Genetically Modified Organisms (GMOs), while the European Union (EU) seeks to establish an alternative regulatory approach. Advances in agricultural biotechnology present complex challenges, involving a wide range of stakeholders, conflicting opinions, and vast amounts of information. As part of the regulatory review process for NGTs, the European Commission (EC) launched a public consultation in 2022 to support the revision of existing regulations. This study applies Association Rule Mining (ARM) to analyze the consultation’s key concerns and policy preferences. Stakeholders—including industry representatives, environmental organizations, scientists, and citizens—have voiced differing opinions. ARM enables the identification of recurring patterns in their responses, highlighting three key themes: sustainability, risk assessment, and transparency. Some consider sustainability an inherent advantage of NGTs, while others view it as irrelevant or as a justification for stricter regulations. Risk assessment and transparency are widely recognized as essential but approached differently—some downplay their importance, while others advocate for more stringent oversight. Additionally, a strategic neutral stance emerges, with certain stakeholders prioritizing risk assessment and transparency without expressing a position on sustainability. The new sustainability-driven regulatory framework may face resistance from those demanding more in-depth evaluations before recognizing NGTs as a sustainable solution. Finally, this paper discusses critical issues related to public consultation processes, highlighting challenges and opportunities in shaping an inclusive and effective regulatory framework.